Flame retardant material for powder bed fusion technology and use of such material in layer-by-layer process

By using powders of low melting point thermoplastic polymers, inorganic flame retardants and other additives, and using powder bed fusion technology to melt, sinter or solidify layer by layer, it is solved that it is difficult to ensure the flame retardant grade when preparing flame retardant molded products in the prior art. The problems of mechanical characteristics and recyclability have achieved efficient and environmentally friendly preparation effects.

CN119490744APending Publication Date: 2025-02-21EMS CHEM AG
View PDF 21 Cites 0 Cited by

Patent Information

Application Number
CN202411149633.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-21
Filing Date
2024-08-21
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

When preparing flame retardant molded products, it is difficult to ensure the standardized flame retardant grade, good mechanical characteristics and recyclability of the components at the same time.

Method used

Use powders consisting of 60% to 99% low melting point thermoplastic polymers (such as polyamide), 1% to 40% inorganic flame retardants (such as Al(OH)3), and 0% to 25% other additives. Molded products with excellent flame retardant properties and mechanical properties are prepared by melting, sintering or curing layer by layer by layer by powder bed fusion technology.

Benefits of technology

Improved recyclability is achieved while retaining the standardized flame retardant grade and good mechanical properties of components made with the powder, especially with an elongation value of at least 10% and avoiding the use of halogen-based flame retardant materials .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005003268570000141
    Figure BDA0005003268570000141
  • Figure BDA0005003268570000161
    Figure BDA0005003268570000161
  • Figure BDA0005003268570000162
    Figure BDA0005003268570000162
Patent Text Reader

Abstract

The present disclosure relates to flame retardant materials for powder bed fusion techniques and the use of such materials in layer-by-layer processes. Powder for producing molded bodies in a layer-by-layer process in which regions of the powder layers are selectively melted, sintered, fused or solidified, the powder consisting of: a) 60 to 99 wt% of a thermoplastic polyamide having a melting temperature of less than 175 DEG C; b) from 1 wt% to 40 wt% of a mineral inorganic flame retardant; c) from 0% to 25% by weight of an additive; wherein the components a) to c) add up to 100% by weight of the total material of the powder.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to powder materials for powder bed fusion (PBF) techniques such as selective laser sintering (SLS), as well as methods for making such materials, selective PBF processes such as laser sintering processes using such materials, and articles made using these materials in SLS processes. Background Art

[0002] The powder bed fusion (PBF) technique is an additive manufacturing process for producing three-dimensional structures by laser sintering starting from a powdered starting material. In this process, an unconsolidated loose powder is present in a container and the workpiece is built up continuously layer by layer by selective irradiation from above with a laser, which irradiates only the areas to be solidified and causes this solidification by melting the material. After the irradiation of the layer and its liquefaction and / or solidification, a subsequent layer of the powdered starting material is laid on top of it, and in a next step, the desired areas in this next layer are melted and, if necessary, solidified and, at the same time, fused with the molten layer below or the solidified layer.

[0003] Specifically, in order to prepare the molded part, the polymer powder is applied in a thin layer to a descendable plate of the sintering chamber, which is usually heated to a temperature slightly below the melting point of the polymer. The layer thickness is selected in such a way that a molten layer is formed during or after the subsequent laser sintering. The laser sinters the powder particles according to the specifications of the control computer. Afterwards, the plate is made to descend by the amount of the layer thickness, usually 0.05mm to 2.0mm. With the application of a new powder layer, the process is repeated. After the preselected number of cycles is completed according to the expected number of layers, a block composed of powder is formed on the outside. Inside, it contains a high viscosity melt or a substantially solidified block in the shape of the desired molded part. The non-melting area where the powder is still in solid form stabilizes the shape of the melt. Afterwards, the block composed of the powder shell and the melt is slowly cooled, and the melt solidifies when the melt is below the solidification temperature of the polymer. It is advantageous if the block is kept at the solidification temperature until the phase change is completed. This is achieved by choosing a low cooling rate within the temperature range of the phase change, so that the heat released by solidification keeps the internal molded body just at the solidification temperature until the phase change is complete. After cooling, the block is removed from the sintering chamber and the molded body is separated from the unsolidified polymer powder. The powder can be used again in the process.

[0004] Commonly used polymer powders for such processes include polyamide 11 (PA11) or polyamide 12 (PA12), polyamide 6 (PA6), but also polyacetal, polypropylene (PP), polyethylene (PE) and ionomers, as described in DE 197 47 309. Polycarbonate (PC) and polystyrene (PS) have also been used.

[0005] EP-A-1 720 930 describes copolymer powders, and the use of such powders for a non-focused molding process, and molded articles made from such polymer powders. The molding process is a layer-by-layer process using powders, in which selective regions of the layers are melted by non-focused introduced electromagnetic energy. The selectivity can be achieved by masks, by applying inhibitors, absorbers, receptors. The PA6 / 12 / 66 system works effectively and specifies MVR values ​​in the range of 1 g / min to 12 g / min.

[0006] EP-A-2 274 363 relates to a process for lowering the crystallization temperature and the melting temperature of polyamide powders resulting from the polymerization of at least one principal monomer, wherein at least one minority comonomer is selected from aminocarboxylic acids, diamine-diacid pairs, lactams and / or lactones, and wherein the at least one minor comonomer represents from 0.1 to 20% by mass of the total mixture of monomers and comonomers, preferably from 0.5 to 15% by mass of the total mixture. Using PA12 / 6 type systems, the proportion of caprolactam in said system must not exceed 20%.

[0007] WO-A-2011124278 relates to a polymer powder for a layer-by-layer process in which the regions of the individual powder layers are selectively fused by introducing electromagnetic energy. The polymer powder comprises: at least one AB-type polyamide, which is prepared by polymerization of a lactam having 10 to 12 carbon atoms in the monomer unit or polycondensation of a corresponding aminocarboxylic acid having 10 to 12 carbon atoms in the monomer unit; and at least one AABB-type polyamide, which is prepared by polycondensation of a diamine and a dicarboxylic acid each containing 10 to 14 carbon atoms in the monomer unit. The present disclosure also relates to: a method for preparing such a powder; a layer-by-layer process for producing a molded body from such a powder, in which the regions of the individual layers are selectively melted by introducing electromagnetic energy, wherein the selectivity is obtained using a mask or by applying an inhibitor, absorber or receptor or by focusing the applied energy; and a molded article produced thereby.

[0008] WO-A-2015009790 describes a component material for printing a three-dimensional component using an electrophotography-based additive manufacturing system, wherein the component material comprises a composition having a semi-crystalline thermoplastic material and a charge control agent. The component material is provided in the form of a powder having a controlled particle size and is configured for use in an electrophotography-based additive manufacturing system having a layer transfer device for printing the three-dimensional component layer by layer. Although different materials for the powder used are mentioned, a specific system is not effective.

[0009] WO-A-2020064825 relates to a sintered powder comprising a first polyamide component and a second polyamide component, wherein the melting point of the second polyamide component is higher than the melting point of the first polyamide component. The disclosure also relates to a method for preparing a molded article by sintering the sintered powder or by an FFF (fused filament fabrication) process and a molded article that can be obtained by the method. The disclosure also relates to a method for preparing a sintered powder. A mixture of aliphatic polyamide and semi-aromatic polyamide is used, and polyamide 6 and polyamide 66 are used as aliphatic polyamides in the mixture.

[0010] CN-A-107337793 introduces a copolymerized nylon powder material for selective laser sintering and a method for manufacturing the same. The method comprises the following steps: copolymerizing a short-chain nylon raw material and a long-chain nylon raw material using the copolymerization reaction principle to obtain a copolymerized nylon resin, crushing the copolymerized nylon resin at low temperature, drying and screening, and adding a flow aid and an antioxidant to obtain a copolymerized nylon powder material, and selective laser sintering is used. A system based on polyamide 1010, polyamide 1212 and polyamide 66 or PA6 in the form of PA6 / 1010, PA66 / 1010, PA6 / 1212, PA66 / 12 is used.

[0011] CN-A-104830053 relates to the field of polymer materials and aims to solve the problem of high industrial cost of nylon 12 in the field of 3D printing. It discloses a method for preparing a caprolactam-laurolactam copolymer modified by glass fiber and its powder, wherein the corresponding mechanical properties of the resulting polymer are described. The copolymer powder has good properties such as thermodynamic properties and dimensional stability, low production cost and use cost, uniform particle size, and can be used to partially replace nylon 12 to a certain extent, especially in the field of 3D printing. The specific system disclosed is only a PA6 / 12 system, and is therefore a system based on caprolactam and laurolactam with glass fiber.

[0012] WO-A-2005082979 discloses polymer powders containing copolymers, the use of such powders in a molding method and molded bodies produced from such polymer powders. The molding method is a method that operates layer by layer using powders, and during the method, regions of the layers are fused by focusing the application of electromagnetic energy. After being cooled, the solidified molded body can be taken out of the powder bed. Compared with molded bodies produced from conventional powders, the component properties of the molded bodies produced using the powders of the invention according to the method can vary within a certain range depending on their composition. The specific systems disclosed are systems comprising PA6 / 12 / 612, PA6 / 12 / 66, PA12 / IPDA12 and polyester systems based on terephthalic acid, wherein IPDA is isophorone diamine.

[0013] US-B-8097333 discloses pre-impregnated composite materials (prepregs) that can be cured to form composite parts with a high level of damage tolerance. The matrix resin comprises a thermoplastic particle component, which is a blend of particles having a melting point above the curing temperature and particles having a melting point at or below the curing temperature. The specific system disclosed is a PA6 / 12 system, and is therefore a system based on caprolactam and laurolactam.

[0014] WO-A-2005105891 relates to a polymer powder comprising a polyamide, its use in a molding process and a molded body made from the polymer powder. The molding process comprises a layering process using a powder, in which selective regions of the relevant layers are fused by introducing electromagnetic radiation. The selectivity can be achieved by masking, applying inhibitors, absorbers or sensitizers, or by focusing the input energy. After cooling, the solidified regions can then be removed from the powder bed as a molded body. Specific systems disclosed include PA12, PA1010, PA1012, PA1212, PA612, PA613.

[0015] WO-A-2016112283 also discloses powder compositions for laser sintering. Nylon copolymer compositions are described that are said to provide enhanced performance in processing and finished products when used in 3D laser sintering processes. Specific systems disclosed include PA11, PA12, PA610 / 6T6I, PA 612 / 6T6I, PA6 / 69, PA 6 / 6T6I.

[0016] WO-A-2007051691 discloses a process for producing ultrafine powders based on polyamide, wherein a polyamide having a relative solution viscosity in the range of 1.5 to 2.0 is contacted with an alcoholic medium in the presence of inorganic particles at superatmospheric pressure and / or elevated temperature to produce at least a partial solution, and the polyamide is subsequently precipitated from the at least partial solution, characterized in that a suspension of inorganic particles in an alcoholic medium is used. The ultrafine polyamide powder obtained has a relative solution viscosity of 1.5 to 2.0 and a relative solution viscosity of 1.5 to 2.0. 2 / g to 100m 2 / g, a specific surface area determined by the BET method, a fineness d50 of less than 70 μm; a bulk density BD in the range of 250 g / l to 1000 g / l; and a particle content of inorganic particles of 0.1 wt % to 80 wt % based on the total weight of the polyamide powder. Specific systems disclosed include PA12, PA1010, and PA1012.

[0017] EP-A-2650106 discloses a polymer powder which exhibits a single melting point determined by differential scanning calorimetry, comprising a polyamide of the AABB type. Specific working systems disclosed include PA1012, PA1010, PA1013, PA613, PA1212.

[0018] WO-A-2009101320 relates to PA polyamide (homopolyamide or copolyamide) powders derived at least in part from renewable materials, wherein the particles have a non-spherical shape and a median volume diameter less than or equal to 20 μm. It also relates to a process for preparing such powders. The specific working systems disclosed include PA11 and PA12.

[0019] EP 23 171 763.8 (not published at the time of priority) discloses a method for producing moldings in a layer-by-layer process, in which regions of a powder layer are selectively melted, sintered, fused or otherwise solidified, characterized in that a thermoplastic ground polyamide powder is used as powder for the powder layer, wherein the polyamide comprises laurolactam and caprolactam (preferably exclusively), and wherein the proportion of caprolactam is in the range from 40 mol % to 60 mol % of the lactam used.

[0020] US20220185991 discloses a method for producing flame-retardant parts by powder bed fusion, wherein the powder comprises at least one polyamide and at least one flame retardant of the cyclic phosphonate type.

[0021] WO2005010087 relates to a powder comprising a polymer and a flame retardant based on ammonium polyphosphate, to the use of said powder for the layered production of moulded bodies, and to moulded bodies produced from said powder. The moulded bodies produced from the powder of the invention have significant advantages over conventional products in terms of their flammability, enabling them to be used in aircraft, for example. Furthermore, the moulded bodies produced from the powder of the invention have improved mechanical properties, in particular in terms of their elastic modulus and tensile strength, compared to moulded bodies based on conventional powders. The density of such moulded bodies is close to that of injection moulded bodies.

[0022] US-A-2022213274 discloses a copolymer powder having a polyamide block and a polyether block. The invention relates to a composition comprising a copolymer powder having a polyamide block and a polyether block, the copolymer being in the form of particles, wherein the powdered filler content is 0% to 10% by mass, and the mass ratio of the polyamide block to the polyether block of the copolymer is less than or equal to 0.7, and the number average molar mass of the polyamide block is less than or equal to 1000 g / mol; and the composition comprises a flow aid having a content greater than or equal to 0.3% by mass. The invention also relates to a method for producing the composition, the use of the composition for constructing a three-dimensional article, and a three-dimensional article manufactured from the composition.

[0023] Ahmad et al. (Polymers 2022, 14(14), 2843; https: / / doi.org / 10.3390 / polym14142843) reported that polymers are being used in many applications around the world. However, there are some disadvantages in the properties of polymers that may hinder their use in certain applications. Therefore, new materials, polymer composites, are introduced. Polymer composites are polymer-based materials with added fillers. Many researchers have reported improvements in polymer properties when fillers are introduced. This helps minimize the disadvantages of using polymers. Therefore, polymer composite products can be used in many industries such as automotive, aerospace, biomedical, and packaging. Fillers derived from natural minerals such as dolomite are one of the best reinforcement materials for polymer materials because they are abundant and low-cost, have high stiffness and hardness, and even have customizable surface chemistry. The use of dolomite as a filler in polymer composite systems has received increasing attention in recent years after researchers successfully demonstrated that dolomite can improve the mechanical, physical, and thermal properties of various polymer materials. However, the original dolomite needs to be chemically or physically treated / modified to prepare it as an effective reinforcing filler. This step helps improve the properties of the resulting polymer composites. This article reviews the use of dolomite as a filler in various polymer materials and how it improves the properties of polymer composites. It also highlights several methods used for the treatment / modification purposes of dolomite. In addition, the role of dolomite as a co-filler or hybrid filler in polymer composite systems is discussed, revealing the great potential and prospects of this mineral filler in the field of polymer composites for advanced applications.

[0024] WO-A-2022106402 relates to a powdered composition comprising: (a) at least one phosphate flame retardant synergist selected from hydrogen phosphate, dihydrogen phosphate, hydrates thereof and mixtures thereof; (b) at least one flame retardant; and (c) at least one thermoplastic polymer. The disclosure also relates to a 3D printed object formed from the powdered composition and a method for forming a 3D printed object. The powdered composition shows good printability, and the 3D printed object obtained from the thermoplastic powder has not only excellent flame retardant properties, but also good mechanical properties. In the embodiments, PA6, PA11 and PA12 systems are shown, all of which have a melting point of at least 180°C or higher.

[0025] US-A-2007197692 relates to a polymer powder containing a copolymer, and to the use of the powder for a molding process, and also to a molded article produced by the polymer powder. The molding process is a layer-by-layer process using a powder, and the region of the corresponding layer is selectively melted via non-focused introduced electromagnetic energy. The selectivity of the energy introduction process can be achieved via a mask, via the application of an inhibitor or an absorber or an acceptor, but it is not intended to limit the invention to this. The powder is preferably used in a process in which selectivity is achieved via the application of an inhibitor or an acceptor or via a masking method. After cooling, the now solidified molded article can be taken out of the powder bed. The properties of the components composed of the molded articles constructed by the method of the invention using the powder of the invention, compared with the molded articles made of conventional powders, and in particular the mechanical properties and thermal properties of the components, can vary widely depending on the composition. In particular, in the case of amorphous copolymers, the proper selection of comonomers can optimize the flow behavior of the molding process. Another advantage is that processing can also be simplified by using the correct copolymer composition. In particular, processing can be performed at relatively low temperatures, simplifying temperature control and accelerating the process. The slower crystallization of semicrystalline copolymers when compared to semicrystalline homopolymers promotes coalescence of molten particles and leads to better shrinkage behavior of molded articles.

[0026] CN-A-112409784 relates to an anti-drip nylon material for selective laser sintering and a preparation method thereof, and the preparation method comprises the following steps: adding a low molecular weight nylon powder, a condensed phase flame retardant metal compound and a coupling agent to a first container, stirring, adding to an extruder, adding a first lubricant, and melt mixing to obtain a mixed nylon material; adding the mixed nylon material, a high molecular weight nylon resin and a second lubricant to an extruder for mixing, and drawing and pelletizing to obtain anti-drip nylon particles; transferring the inorganic filler and the anti-drip nylon particles to a cryogenic pulverizer for processing and pulverizing to obtain an anti-drip nylon semi-finished product powder, and adding the anti-drip nylon semi-finished product powder, a flow aid and an antioxidant to a second container for stirring to obtain an anti-drip nylon material for selective laser sintering. The condensed phase flame retardant metal compound has a good degree of dispersion in the low molecular weight nylon powder, and the finished material has a good anti-drip effect and mechanical properties. Summary of the invention

[0027] An object of the present invention is to propose a powder for a powder bed fusion method (e.g. an SLS method of the type described above). The powder bed fusion method may include the use of focused or non-focused input electromagnetic energy, thermal energy or other energy to selectively fuse, melt, sinter or solidify powder materials during additive manufacturing. Preferably, the powder is used to produce fire-resistant articles / moldings in a layer-by-layer process, in which regions of the powder layer are selectively melted using focused or non-focused input electromagnetic energy. It can be used in an SLS process, as well as in a multi-jet fusion (MJF), selective absorption fusion (SAF) or high speed sintering (HSS) process, wherein the resulting parts exhibit good to excellent flame retardancy according to industry standards (UL-94V).

[0028] A powder according to the present invention is defined as a solid substance which has been reduced (at room temperature) to a fine loose particle state, for example by crushing, grinding, breaking, settling or a combination thereof.

[0029] According to a first aspect of the invention, it relates to a powder for producing a moulding as defined in claim 1, in particular a powder for producing a moulding in a layered process in which regions of a powder layer are selectively

[0030] (1) Melting by input electromagnetic energy (usually via a controllable laser),

[0031] (2) melting by thermal energy input from a source other than electromagnetic energy, or

[0032] (3) Otherwise melted, fused, sintered or solidified to form a product or article.

[0033] More specifically, it relates to a powder for producing a moulding in a layer-by-layer process in which regions of the powder layers are selectively melted, sintered, fused or solidified, wherein the powder consists of the following components:

[0034] a) thermoplastic polymers (e.g. selected from polyamides, polyesters, polyethylene, polypropylene, polyurethanes, or copolymers and / or mixtures thereof, in particular polyamides) having a melting temperature (measured as further defined below) of less than 175°C, preferably less than 160°C;

[0035] b) 1 to 40% by weight of an inorganic flame retardant (in particular a halogen-free flame retardant, preferably the inorganic flame retardant is a mineral, i.e. a chemical composition and a crystal structure which occurs in nature in particular in substantially pure form), usually an inorganic flame retardant which starts to activate and / or decompose at a temperature of at most 260° C.;

[0036] c) 0 to 25% by weight of additives other than a) and b);

[0037] The components a) to c) add up to 100% by weight of the powder material.

[0038] As can be seen from the lower limit of the proportion of component a), the powder material is subject to the condition that the sum of components B) and C) does not account for more than 40% of the total weight of the powder material.

[0039] The invention also relates to and claims the use of such a powder.

[0040] The proposed SLS powder solves the following problems associated with current technologies:

[0041] It offers improved recyclability while retaining the standardized flame retardant rating of the resulting parts made using the powder, which is not achievable using existing materials;

[0042] It provides good mechanical properties to parts made using the powder, in particular elongation at break values ​​of at least 10% or greater;

[0043] It provides good post-processing characteristics (no or significantly reduced red streaks);

[0044] It provides good printability (especially low warpage);

[0045] • It avoids the use of halogen based flame retardant materials.

[0046] The important elements of the present invention are as follows, selected individually or in combination:

[0047] · Use lower melting point polymers (e.g., T m <160°C) enables preferably mineral based flame retardants (e.g. Al(OH)3) which activate / decompose at >160°C, enabling easier printing and part quality;

[0048] ·Use polymers with lower melting points (such as T m <160°C) ensures lower printing temperatures, which reduces the decomposition of non-mineral-based flame retardant additives;

[0049] ·Use polymers with lower melting points (such as T m <160°C) ensures lower printing temperatures and thus improves the recyclability of used powders;

[0050] Utilizing preferably mineral-based flame retardants in SLS printing does not interfere with laser absorbing flame retardants (e.g. polyphosphinates), thereby allowing production of parts;

[0051] Using, for example, copolyamides or low crystallinity (crystallinity: <35%) polymers enables higher flame retardant material loadings (e.g. >10%) to ensure high flame retardancy at minimal wall thickness (e.g. 1 mm to 2 mm) while retaining good printability and good mechanical properties (1% to 40% or 1% to 30% flame retardant loading, preferably 10% to 25%);

[0052] Utilizing a combination of flame retardant materials and fillers (e.g. glass fibers) enables improvement of mechanical properties and flame retardancy (additives: 0% to 25%, preferably 5% to 15%);

[0053] Utilization of poorly soluble flame retardant materials such as Al(OH)3 enables effective post-treatment by steam smoothing.

[0054] According to a first preferred embodiment, the crystallinity of the thermoplastic polymer is lower than 35%, preferably lower than 30%.

[0055] According to a further preferred embodiment, the thermoplastic polymer is a semicrystalline polyamide, preferably based on aromatic and / or aliphatic dicarboxylic acids and / or aromatic and / or aliphatic diamines, including cycloaliphatic diamines, and / or aromatic and / or aliphatic lactam / aminocarboxylic acid structural units.

[0056] According to a preferred embodiment, the semi-crystalline polyamide is a polyamide free of polyether blocks.

[0057] According to a preferred embodiment, the powder used for producing the moldings does not contain inorganic flame retardants having a decomposition temperature above 350°C or above 400°C, or above 500°C or even above 600°C.

[0058] According to a preferred embodiment, the powder used for producing the moldings contains no dolomite (anhydrous carbonate mineral consisting of calcium magnesium carbonate, such as in particular CaMg(CO 3 ) 2 ) neither as an inorganic flame retardant (b) nor as an additive (c).

[0059] According to another preferred embodiment, the powder for producing the moldings contains no phosphate-based flame retardants or synergists, neither as inorganic flame retardants (b) nor as additives (c), preferably the powder for producing the moldings contains no ammonium polyphosphate (APP).

[0060] The aromatic and / or aliphatic (including cycloaliphatic) diamines are preferably selected from linear or branched aliphatic, cycloaliphatic or aromatic diamines having 4 to 20 carbon atoms.

[0061] The linear aliphatic diamine is preferably selected from linear aliphatic diamines having 6 to 12 carbon atoms, preferably from the group of tetramethylenediamine, hexamethylenediamine, octanediamine, nonanediamine, decanediamine, or mixtures thereof.

[0062] The alicyclic diamine is preferably selected from bis(4-amino-3-methylcyclohexyl)methane (MACM, CAS No. 6864-37-5), bis(4-aminocyclohexyl)methane (PACM, CAS No. 1761-71-3), or a mixture thereof.

[0063] The aromatic diamine is preferably selected from xylylenediamine, in particular p-xylylenediamine, m-xylylenediamine, or a mixture thereof.

[0064] The aromatic and / or aliphatic dicarboxylic acids are preferably selected from the group of linear or branched aliphatic, cycloaliphatic or aromatic dicarboxylic acids having 4 to 20 carbon atoms, wherein preferably the linear aliphatic dicarboxylic acids are selected from succinic acid, adipic acid, suberic acid, sebacic acid, dodecanoic acid, or mixtures thereof, and wherein the aromatic dicarboxylic acids are selected from terephthalic acid, isophthalic acid, or mixtures thereof.

[0065] Preferably, the polyamide is a copolyamide comprising caprolactam structural units, preferably with further structural units based on linear aliphatic lactams / aminocarboxylic acids and / or linear aliphatic dicarboxylic acids and linear aliphatic diamines, at least one of which preferably has at least 9 carbon atoms.

[0066] Further preferably, the polyamide is selected from the group consisting of PA6 / 6I, PA6 / 66, PA6 / 66 / 6I, PA 6 / 106 / 12, PA 6 / 610, PA 6 / 610 / 12, PA 6 / 612 / 12, PA6 / 1010 / 12, PA 6 / 1012 / 12, PA6 / 12, PA6 / 106, PA6 / 1010, PA6 / 1012, PA6 / 69 or a mixture thereof, preferably selected from PA6 / 12, PA6 / 106, PA6 / 1010, PA6 / 1012, PA6 / 69 or a mixture thereof, wherein preferably, in order to adapt to the melting temperature, the molar proportion of caprolactam is at most 70%, preferably at most 60% or in the range of 30% to 70%, wherein the molar proportion of caprolactam is in the case of PA6 / 12 relative to the total amount of lactam used and in other cases (for example in the case of PA6 / 106, PA6 / 1010, PA6 / 1012, PA6 / 69) relative to the total amount of lactam and diamine-dicarboxylic acid blocks used.

[0067] The thermoplastic polyamide powder preferably contains no aromatic structural units.

[0068] According to a further preferred embodiment, the thermoplastic polymer is selected as polyamide PA 6 / 12 or a copolymer thereof, wherein the molar proportion of laurolactam is at least 20%, preferably at least 25%, preferably in the range of 30 to 70% or 40 to 50%, wherein the molar proportion of laurolactam is relative to the total amount of lactam used.

[0069] According to a further preferred embodiment, the thermoplastic polymer is chosen as polyamide PA 6 / 12 or a copolymer thereof, wherein the molar proportion of caprolactam is at least 20%, preferably at least 25%, preferably in the range of 30% to 70%, wherein the molar proportion is relative to the total amount of lactam used.

[0070] According to another preferred embodiment, the thermoplastic polymer has at least one of the following properties:

[0071] a melting point measured according to ISO 11357 of less than 175°C, less than 170°C or less than 160°C or less than 150°C or less than 140°C, preferably in the range of 100°C to 155°C or 120°C to 140°C,

[0072] is a ground or milled polyamide powder, and wherein preferably in the case of a ground powder it is produced by a cryogenic grinding process,

[0073] having a relative viscosity in the range of 1.5 to 2.1, preferably in the range of 1.6 to 2.0, said relative viscosity being preferably measured in m-cresol according to ISO 307 at a temperature of 20° C. and a concentration of 0.5% by weight,

[0074] • Having a melting enthalpy measured according to ISO 11357 of less than 20 J / g, preferably less than 10 J / g.

[0075] According to a further preferred embodiment, the proportion of the thermoplastic polymer of component a) is in the range from 65% to 95% by weight, preferably in the range from 70% to 90% by weight or from 70% to 80% by weight, in each case relative to the total material of the powder.

[0076] According to another preferred embodiment, the inorganic flame retardant starts to activate and / or decompose at a temperature of at most 260°C or at most 200°C, preferably at most 190°C, wherein preferably the inorganic flame retardant is activated and / or decomposed in a temperature range of 170°C to 260°C or 170°C to 350°C, preferably in a range of 180°C to 260°C or 180°C to 340°C.

[0077] The inorganic flame retardant is preferably a nitride, preferably selected from BN, ZnB or a mixture thereof, and / or a metal hydroxide, preferably selected from aluminum hydroxide (Al(OH)3, also known as ATH), basic magnesium carbonate (MgCO3·Mg(OH)2, also known as BMC), magnesium hydroxide (Mg(OH)2), or a combination thereof, wherein the inorganic flame retardant is preferably selected as aluminum hydroxide.

[0078] Typically, the proportion of the inorganic flame retardant of component b) is in the range from 5% to 30%, preferably in the range from 10% to 25%, most preferably in the range from 15% to 25%, in each case relative to the total material of the powder.

[0079] The additives of component c) are different from component b) and can be selected from the group of fillers, preferably from the group of talc, fillers based on aluminum oxide, glass fillers (preferably glass fibers and / or glass beads), calcium carbonate; flow agents, preferably from the group of fumed or precipitated silica, metal salts of long-chain fatty acids, including metal stearates, titanium dioxide, Group 1 salts, aluminum oxide; flame retardant systems different from component b), flame retardant synergist compounds (e.g., metal oxides, borates, nitrides, organophosphorus and cyanurates, in each case different from b)), preferably containing nitrogen and / or phosphorus, including melem, melam, cyanuramide or other melamines or their derivatives, such as melamine polyphosphates.

[0080] For example, in some embodiments, the powder for additive manufacturing described herein comprises a flow aid component. Therefore, in order to achieve enhanced fluidity of the powder during layer fusion, a small amount of flow agent or a combination of flow agents can be used. Such flow agents are, for example, talc, Al-based flow aids, glass fillers, CaCO3 (or other metal carbonates), Aerosil (pyrogenic or precipitated silica), Sipernat variants, Mg stearate (or other stearates), TiO2 (or other metal oxides), Group 1 salts, and metal-based long-chain fatty acids.

[0081] It is also possible to have a coating on the thermoplastic polyamide powder particles, which coating has corresponding additives which support the additive manufacturing process.

[0082] Preferably, the thermoplastic (polyamide) powder is a ground or precipitated (polyamide) powder and preferably, in the case of a ground powder, it is produced by a cryogenic grinding process.

[0083] The powder preferably has an average particle size D50 in the range of 50 to 80 μm, preferably in the range of 50 to 65 μm, more preferably in the range of 50 to 60 μm, the average particle size D50 being preferably measured according to ISO 13322-2.

[0084] Preferably, the particle size distribution is such that 80%, preferably 90%, of the particles are located in the size range of 20 μm to 100 μm, preferably in the range of 40 μm to 90 μm.

[0085] Preferably, the D10 value measured according to ISO 13322-2 is in the range of 15 to 45 μm, preferably in the range of 20 to 30 μm, and / or the D95 value measured according to ISO 13322-2 is in the range of 80 to 150 μm, preferably in the range of 85 to 98 μm.

[0086] Typically, the powder and / or the thermoplastic polyamide powder has a diameter D50 measured according to ISO 13322-2 of 50 to 80 μm, preferably 50 to 65 μm, more preferably 50 to 60 μm.

[0087] The powder particles preferably have substantially a slightly jagged or irregular shape (eg, sphericity much less than 1), a spherical shape, or a potato shape.

[0088] The thermoplastic ground polyamide powder preferably has an MFR value in the range of 6 to 17 g / 10 min, said MFR value preferably being measured according to ISO 1133. According to another aspect of the present invention, it relates to a process for preparing a powder as defined above, wherein after melt mixing components a) to c), the thermoplastic material is subjected to a cryogenic grinding process or a precipitation process and subsequently to a particle size screening process, preferably for producing a particle size distribution such that the average particle size D50 is in the range of 50 to 80 μm, preferably in the range of 50 to 65 μm, more preferably in the range of 50 to 60 μm, said average particle size D50 preferably being measured according to ISO 13322-2.

[0089] In one example, the method is characterized in particular by achieving a particle size distribution suitable for the printing process by a suitable sieving technique (drum-type air-jet screen, ultrasonic drum or air classifier). In other examples, the method may not use sieving techniques.

[0090] In addition, in some examples, if desired, after mixing with additives, the method includes forming the thermoplastic polyamide powder using solvent precipitation, solvent pulverization, melt emulsification, melt pulverization or another micronization technique. In addition, in some embodiments, the composition for additive manufacturing can be prepared by blending the polyamide powder with one or more additional components or additives (e.g., additives or fillers). In some examples, such a composition can be prepared by dry blending or wet blending.

[0091] According to another aspect of the present invention, it relates to a method for printing a three-dimensional article, comprising the following steps:

[0092] providing a powder as defined above; and

[0093] selectively solidifying layers of said powder to form an article, preferably using focused or unfocused input electromagnetic energy, wherein preferably the powder is provided in a layer-by-layer process,

[0094] Preferably, the powder has a particle size D50 measured according to ISO 13322-2 of 50 to 80 μm, preferably 50 to 65 μm, more preferably 50 to 60 μm.

[0095] According to another aspect of the present invention, it relates to a flame retardant article prepared using the method as defined above.

[0096] According to another aspect of the invention, it relates to the use of a powder as defined above for producing a moulding in a layer-by-layer process, wherein regions of the powder layers are selectively melted, sintered, fused or solidified, preferably by focused or unfocused input electromagnetic energy.

[0097] Further embodiments of the invention are given in the dependent claims. DETAILED DESCRIPTION

[0098] The following describes preferred embodiments of the present invention based on embodiments, which are only used as illustrations and should not be construed restrictively. According to the present invention, condensation reactions and grinding processes and uses are described.

[0099] All materials including the comparative material (VB) were produced by first compounding the particles and then producing the powders.

[0100] Step 1 - Production of PBF flame retardant polymer composition for 3D printing process

[0101] will have a low melting point (e.g., T mThe polymer (Poly) with a temperature of 160°C <160°C is compounded with a flame retardant (FR) and the presence or absence of a filler (F) in a specific ratio on a twin-screw extruder ZSK-30 / 2 from Werner & Pfleiderer at 160°C to 200°C. The compounding process is carried out below the activation temperature of the flame retardant but above the melting point of the polymer.

[0102] Table 1 summarizes the flame retardant PBF polymer compositions according to the present invention, and Table 2 summarizes the comparative PBF polymer compositions.

[0103] Table 1: Flame retardant PBF polymers according to the invention

[0104] B1 B2 B3 B5 B6 B7 Polymer PA6 / 12 PA6 / 12 PA6 / 12 PA6 / 106 PA6 / 106 PA6 / 106 Flame retardant (FR) <![CDATA[Al(OH)3]]> <![CDATA[Al(OH)3]]> <![CDATA[Al(OH)3]]> <![CDATA[Al(OH)3]]> <![CDATA[Al(OH)3]]> <![CDATA[Al(OH)3]]> Filler(F) - GB GB - GB aluminum Ratio (Poly / FR / F) 75 / 25 / 0 75 / 15 / 10 65 / 25 / 10 75 / 25 / 0 67.5 / 13.5 / 10 65 / 25 / 10

[0105] Table 2: Comparison of PBF polymers

[0106]

[0107] polymer:

[0108] PA6 / 12: Copolymer resulting from the polymerization of a mixture of caprolactam (56.6 mol %) and laurolactam (43.4 mol %). m : 130° C., crystallinity <29%, melting enthalpy <10 J / g). Caprolactam (40.2 kg) and laurolactam (53.7 kg) were transferred to an autoclave with water (3.95% by weight), where the mixture was stirred at 190° C. to 200° C. for 120 minutes. The mixture was then heated to 270° C. and 20 bar and stirred at 290° C. for 5 hours at a constant pressure of 20 bar. After 4 hours, the polymer was cooled to 270° C. and the pressure was reduced to 0.3 bar. The temperature was subsequently reduced to 260° C. The polycondensate was then granulated and dried according to standard procedures.

[0109] PA6 / 106: Copolymer resulting from the polymerization of caprolactam (70 mol%) with 1,10 diamine and adipic acid (mixture of diamine and diacid 1:1, 30 mol% diamine-dicarboxylic acid blocks). Resulting properties: T m: 153.23 ° C, crystallinity <29%, melting enthalpy <20.31 J / g. Synthetic example: Caprolactam (43.08 kg) and 1,10 diamine (28.10 kg), adipic acid (23.83 kg) were transferred to an autoclave with water (9% by weight), where the mixture was stirred at 180 ° C to 200 ° C for 160 minutes. The mixture was then heated to 200 ° C and 20 bar and stirred at 270 ° C for 4 hours at a constant pressure of 20 bar. After 4 hours, the polymer was cooled to 260 ° C and the pressure was reduced to 0.3 bar. The temperature was then reduced to 260 ° C, and the polycondensate was taken out of the reactor and then granulated and dried according to standard procedures.

[0110] PA12: Tm: 178°C, melting enthalpy 35 J / g to 45 J / g.

[0111] Flame retardant:

[0112] Al(OH)3: provided by Huber Advanced Materials.

[0113] Exolit OP1230: Clariant, CAS No. 225789-38-8, starts to activate and decompose at temperatures of at least 300°C.

[0114] Synergists:

[0115] APP: non-mineral builder, ammonium polyphosphate, provided by Clariant (AP 422: VB3, AP 766: VB4) or Distona (MFLAM AP120: VB2., CAS No.: 68333-79-9), starts to activate and decompose at a temperature of at least 300°C.

[0116] filler:

[0117] GB: Glass beads <20 μm, supplied by Potters Industries

[0118] Aluminum filler: AlSi10Mg powder supplied by Carpenter Additive.

[0119] Step 2 - Produce powder by grinding:

[0120] The pellets obtained from step 1 were ground into the original ground material at -50°C using a Hosokawa 160C pin mill with addition of liquid nitrogen in reverse operation.

[0121] Subsequently, the raw ground material was separated by ultrasonic sieving into a particle size distribution of about 40 μm to 90 μm using a sieving fabric of corresponding mesh size.

[0122] Analysis: Measured particle size distribution (μm): D10: 30 to 40, D50: 45 to 60, D95: 80 to 100, as determined on a Camsizer XT according to ISO 13322-2; crystallinity <29%.

[0123] Step 3: SLS Molding:

[0124] The powder obtained from step 2 was printed using an SLS printer SPro60 from 3D Systems (equipped with a CO2 laser) to produce a test body (ISO 527, ISO / CD 3167 type B1). A combustion test was carried out in accordance with the standard (UL-94V) using plates of different thicknesses: 280 mm×240 mm×(1 mm to 5 mm). A lightweight paper-based fabric was placed under the sample to observe whether any flame development occurred. An intense blue flame was maintained at a distance of 20 mm from the part for 10 seconds, the burning time as well as any dripping development (burning or self-extinguishing) was recorded, and then the part was exposed to the flame again for another 10 seconds and the flammability / dripping development or development was recorded.

[0125] For Examples B1 to B7 according to the invention and Comparative Examples VB1 to VB8, the printer was set up with the parameters given in the following Table 3. Table 4 summarizes the mechanical properties, and Tables 5 and 6 summarize the flame retardant properties.

[0126] Table 3: Compounds and SLS parameters for printed samples

[0127]

[0128]

[0129] WD: preheating duration; PBT: part bed temperature; FT: feed temperature; LP: laser parameters: filling laser power (W), profile laser power (W), microtome filling scan spacing (mm), ': single scan; ': double scan; CD: cooling (time); *: in contrast to all other experiments, VB8 was performed with a laser speed of 6 m / s, while in all other cases a laser speed of 12 m / s was used.

[0130] Comments on VB7: It has 25% Al(OH)3, noticeable warping was noted, parts were difficult to print, but just enough to perform flame retardant testing and determine mechanical properties.

[0131] Table 4: Mechanical properties of printed examples

[0132]

[0133]

[0134] All materials were measured after conditioning at 23°C and 50% humidity for 40 hours; X in VB5 indicates that the corresponding printing example could not be produced because the powder starting material was not suitable for the SLS process and no parts could be produced; Natural color is defined as white with slight translucency (visually). White is defined as colorless without translucency (visually). Fragile parts are defined as parts that are poorly sintered when the wall thickness is ≥1mm (for example, easily torn from the FR board). Failure is defined as no sintering (no parts produced) or problems with warping that prevent reliable measurements from being obtained.

[0135] Table 5: Overview of flame retardancy according to industry standard UL-94V

[0136]

[0137]

[0138] The X in VB5 indicates that the corresponding print example could not be produced because the powder starting material was not suitable for the SLS process and the part could not be produced; the unsintered powder of each material was removed from the printer, sieved out and reprinted. The flame retardancy test was repeated and the same results as presented above were obtained.

[0139] Table 6: Overview of flame retardancy according to industry standard UL-94V after vapor smoothing by AMT-Vapor Smoothing Technology

[0140] B1 – Steam Smoothing B2 – Steam Smoothing Compound Basics: <![CDATA[AL(OH)3]]> <![CDATA[AL(OH)3 / GB]]> Exposure times 2 2 Exposure duration (seconds) 10 10 Optimum component thickness (mm) 1 2 Burning time (seconds) <10 <10 Drops Y Y Self-extinguishing dripping Y Y Rating V0@1mm V0@2mm

[0141] method:

[0142] Characteristics of starting polyamide materials:

[0143] Melting point and melting enthalpy: Melting point T measured on pellets or powders m and the melting enthalpy (second melting peak TM2) are determined according to ISO standards 11357-1 (2016), 11357-2 (2013) and 11357-3 (2011), where differential scanning calorimetry (DSC) is performed at a heating rate of 10°C / min and the values ​​are from the second temperature cycle.

[0144] Characteristics of powder materials and printed parts:

[0145] Crystallinity of PA6 / 12 and PA6 / 106 powders: Determined by powder X-ray diffraction (PXRD) on a Rigaku MiniFlex-600C using the following parameters:

[0146] Instrument configuration:

[0147] Goniometer: 150 mm radius; X-ray source: Cu Kα Incident Soller slit: 2.5°; length limiting slit: 10 mm; divergence slit: 0.625°; accessories: ASC-8; scattering slit: none; receiving Soller slit: 2.5°; receiving slit: none; monochromatization: Kβ filter (x1.5) (Ni); detector: D / teXUltra2.

[0148] Measurement conditions:

[0149] Voltage–current: 40 kV–15 mA; scanning axis: θ / 2θ; scanning mode: 1D scanning; scanning range: 3.5° to 70°; scanning speed: 15° / min; sampling step: 0.1°.

[0150] The degree of crystallinity was calculated using the degree of crystallinity (DoC) method, which compares the sum of the intensities of all crystalline peaks (Bragg) to the total scattered intensity to estimate the amorphous concentration.

[0151] Flowability is assessed visually by the degree of filling of the part after recoating: excellent: completely filled, good: some parts with minor defects. Flowability means that a defect-free powder bed results from the insertion of the next powder layer, e.g. so that the powder does not clump.

[0152] The tensile modulus is measured according to ISO 527 at a temperature of 23° C. using an ISO tensile bar (standard: ISO / CD 3167, type A1, 170×20 / 10×4 mm) with a pulling speed of 1 mm / min.

[0153] Tensile strength and elongation at break were measured according to ISO 527 at a temperature of 23° C. using an ISO tensile bar (standard: ISO / CD 3167, type A1, 170×20 / 10×4 mm) with a tensile speed of 5 mm / min.

[0154] The Charpy impact strength is measured according to ISO 179 / *eA at 23° C. on an ISO test bar (according to standard: ISO / CD 3167, type B1, 80×10×4 mm).

[0155] Surface quality finish as well as cracks, warping and curling are visually assessed. Cracking is the appearance of cracks in the powder bed when a new powder layer is pushed, which means that the area below is lasered multiple times and in the best case only cracks appear in the finished component, but agglomerations in the powder bed are also possible, which can ruin the entire printing process. Curling refers to deformations at the edges of a component, for example, during laser processing. Warping, on the other hand, refers to deformations over the entire component, which usually occurs when the laser bed cools down, i.e. only after the laser is applied.

[0156] Flame retardant test UL 94-V: Print a strip of 280 mm × 240 mm × X mm (where X = 1 mm, 2 mm, 3 mm, 4 mm, or 5 mm) by the above method. The strip is suspended at a distance of 20 mm above a strong blue butane flame (the part is surrounded by a lighter blue flame) for 10 seconds. The flame is removed and the duration of the burning is timed, while noting whether the drips formed are self-extinguishing. After the flame has been extinguished or extinguished, if possible, the part is re-exposed to the flame for another 10 seconds and the observation is repeated. For each sample, all wall thicknesses are tested. The best performing thickness is recorded in Table 2 in the form of a rating.

[0157] Steam smoothing (by AMT Technology): carried out using a post-pro SF 100 from amt. Standard settings for copolyamides were used.

[0158] Results and Discussion:

[0159] As can be seen from the evidence in the table, the ability of PA6 / 12 as well as PA6 / 106 to perform well in the flame retardancy test standard UL 94V is significantly improved by the inclusion of a mineral-based flame retardant. The presence of glass enables the amount of flame retardant required to reach V0 at 2 mm to be reduced, however glass alone is not suitable for inhibiting flame retardancy. In all embodiments, flowability is good, and for all embodiments according to the invention, printability is good. With 0% of the original powder added, there is no loss of printing performance or flame retardancy (only partial agglomeration and overflow) for the entire print. In addition, it should be noted that the mechanical values ​​are for conditioned (40 hours, 50% humidity, at 23°C) parts that maintain good mechanical properties. In addition, the parts can be steam-smoothed well compared to other standard materials, giving the flame retardant material more applications.

Claims

1. A powder for producing a moulding in a layer-by-layer process in which regions of the powder layers are selectively melted, sintered, fused or solidified, The powder is composed of the following components: a) 60 to 99% by weight of a thermoplastic polymer, the thermoplastic polymer being selected from at least one polyamide having a melting temperature of less than 175° C.; b) 1 to 40% by weight of a mineral inorganic flame retardant; c) 0 to 25% by weight of additives other than a) and b); The components a) to c) add up to 100% by weight of the total material of the powder.

2. Powder according to claim 1, wherein the thermoplastic polymer has a crystallinity lower than 35%, preferably lower than 30%.

3. Powder according to claim 1, wherein the thermoplastic polymer is a semicrystalline polyamide, preferably based on aromatic and / or aliphatic dicarboxylic acids and / or aromatic and / or aliphatic diamines and / or aromatic and / or aliphatic lactam / aminocarboxylic acid structural units, the aliphatic diamines including cycloaliphatic diamines, wherein preferably the polyamide is a copolyamide comprising caprolactam structural units, preferably with further structural units based on linear aliphatic lactam / aminocarboxylic acid and / or linear aliphatic dicarboxylic acid and linear aliphatic diamine, at least one of which preferably has at least 9 carbon atoms, and It is further preferred that the polyamide is selected from the group consisting of PA 6 / 6I, PA 6 / 66, PA6 / 66 / 6I, PA 6 / 106 / 12, PA6 / 610, PA 6 / 610 / 12, PA 6 / 612 / 12, PA 6 / 1010 / 12, PA 6 / 1012 / 12, PA 6 / 12, PA 6 / 106, PA6 / 1010, PA 6 / 1012, PA 6 / 69 or mixtures thereof, in particular PA 6 / 12 or PA 6 / 106 or mixtures thereof, wherein preferably the molar proportion of caprolactam is at most 70%, preferably at most 60%, preferably in the range of 30 to 70%, wherein the molar proportion of caprolactam is in the case of PA 6 / 12 relative to the total amount of lactam used and in the other cases relative to the total amount of lactam and diamine-dicarboxylic acid blocks used.

4. Powder according to any of the preceding claims, wherein the thermoplastic polymer is selected as polyamide PA 6 / 12 or a copolymer thereof, wherein the molar proportion of laurolactam is at least 20%, preferably at least 25%, preferably in the range of 30% to 70%, wherein the molar proportion of laurolactam is relative to the total amount of lactam used.

5. A powder according to any one of the preceding claims, wherein the thermoplastic polymer has a melting point measured according to ISO 11357 of less than 170°C or less than 160°C or less than 150°C or less than 140°C, preferably in the range of 100 to 155°C or 120 to 140°C, and / or is a ground or precipitated polyamide powder, and wherein preferably in the case of a ground powder, the thermoplastic polymer is produced by a cryogenic grinding process, and / or having a relative viscosity in the range of 1.5 to 2.1, preferably in the range of 1.6 to 2.0, preferably measured in m-cresol according to ISO 307 at a temperature of 20° C. and a concentration of 0.5% by weight, and / or having a melting enthalpy measured according to ISO 11357 of less than 25 J / g or less than 20 J / g, preferably less than 10 J / g.

6. Powder according to any of the preceding claims, wherein the proportion of the thermoplastic polymer of component a) is in the range from 65% to 95% by weight, preferably in the range from 70% to 90% by weight or from 70% to 80% by weight, in each case relative to the total material of the powder.

7. The powder according to any one of the preceding claims, wherein the inorganic flame retardant starts to activate and / or decompose at a temperature of at most 260°C or at most 200°C, preferably at most 190°C, wherein preferably the inorganic flame retardant is activated and / or decomposes in a temperature range of 170°C to 350°C or 170°C to 260°C, preferably in a range of 180°C to 340°C or 180°C to 240°C.

8. The powder according to any one of the preceding claims, wherein the inorganic flame retardant is a nitride, preferably selected from BN, ZnB or mixtures thereof and / or a metal hydroxide, preferably selected from aluminum hydroxide (Al(OH)3), basic magnesium carbonate (MgCO3·Mg(OH)2), magnesium hydroxide (Mg(OH)2) or a combination thereof, wherein preferably the inorganic flame retardant is selected as aluminum hydroxide.

9. A powder according to any of the preceding claims, wherein the proportion of the inorganic flame retardant of component b) is in the range of 5% to 30%, preferably in the range of 10% to 25%, most preferably in the range of 15% to 25%, in each case relative to the total material of the powder.

10. A powder according to any one of the preceding claims, wherein the additives of component c) are different from component b) and are selected from: fillers, preferably selected from the group of talc, fillers based on alumina, glass fillers, preferably glass fibers and / or glass beads, calcium carbonate; flow agents, preferably selected from the group of pyrogenic or precipitated silica, metal salts of long-chain fatty acids, including metal stearates, titanium dioxide, Group 1 salts, aluminum oxides; flame retardant systems different from component b), flame retardant synergist compounds, preferably containing nitrogen and / or phosphorus, including melem, melam, cyanuramide or other melamines or their derivatives.

11. Powder according to any of the preceding claims, wherein the powder has an average particle size D50 in the range of 50 to 80 μm, preferably in the range of 50 to 65 μm, more preferably in the range of 50 to 60 μm, the average particle size D50 being preferably measured according to ISO 13322-2, and / or wherein the thermoplastic ground polyamide powder has an MFR value in the range of 6 to 17 g / 10 min, said MFR value being preferably measured according to ISO 1133.

12. A method for preparing a powder according to any one of the preceding claims, wherein: After melt mixing of components a) to c), the thermoplastic material is subjected to a cryogenic grinding process or a precipitation process and subsequently to a particle size screening process, preferably for producing a particle size distribution such that the average particle size D50 is in the range of 50 μm to 80 μm, preferably in the range of 50 μm to 65 μm, more preferably in the range of 50 μm to 60 μm, the average particle size D50 being preferably measured according to ISO 13322-2.

13. A method for printing a three-dimensional product, comprising the following steps: Providing a powder according to any one of claims 1 to 11; and selectively solidifying layers of said powder to form said article, preferably using focused or unfocused input electromagnetic energy, wherein preferably said powder is provided in a layer-by-layer process, Preferably, the powder has a particle size D50 measured according to ISO 13322-2 of 50 μm to 80 μm, preferably 50 μm to 65 μm, more preferably 50 μm to 60 μm.

14. A flame retardant article produced using the method defined in claim 13.

15. Use of a powder according to any one of claims 1 to 11 for producing mouldings in a layer-by-layer process in which regions of powder layers are selectively melted, sintered, fused or solidified, preferably by focused or unfocused input of electromagnetic energy.

Citation Information

Patent Citations

  • Caprolactam-laurolactam co-polymer modified by glass fiber and preparation method of powder thereof

    CN104830053A

  • Copolymerized nylon powder material used for selective laser sintering, and preparation method thereof

    CN107337793A

  • Anti-dripping nylon material for selective laser sintering and preparation method thereof

    CN112409784A

  • use of a polyamide 12 for selective laser sintering

    DE19747309A1

  • Polymer powder comprising a copolymer, use in a shaping method which uses a non-focussed application of energy and moulded body that is produced from said polymer powder

    EP1720930A1